The Author's Handwritten Miscellany of the End of 19th Century of the Old Believer Monk Cyprian (Sozonov) - Melnikov, Ilya (Slavistica Vilnensis, 2021)
The publication contains information about the Old Believer scribe of Phedoseevtzy congregation of the second half of 19th century monk Cyprian and a description of the author's miscellany compiled by him. The content of the manuscript, entitled "Katolog" by the monk, is interesting both in terms of the volume of sources involved and in terms of topics. The collection reflects the doctrinal position of Cyprian, which manifested itself in the activities of the sketes at the Moscow outpost in St. Petersburg and on Ilyushkin Island, which were headed by a monk.
Keywords: old-belief; manuscripts; Theodosians; monasticism